Successful outcome of second allogeneic bone marrow transplantation for blastic plasmacytoid dendritic cell neoplasm with MYC locus rearrangement. (2019) - Kato, Takeharu; Itonaga, Hidehiro; Taguchi, Jun; Makiyama, Junya; Fujioka, Machiko; Taguchi, Masataka; Horai, Makiko; Sawayama, Yasushi; Niino, Daisuke; Imaizumi, Yoshitaka; Hata, Tomoko; Yoshida, Shinichiro; et al.
Abstract: A 62-year-old male was diagnosed with blastic plasmacytoid dendritic cell neoplasm (BPDCN) with a MYC rearrangement. Four months after the first unrelated bone marrow transplantation (BMT), he developed the relapsed BPDCN. After the achievement of partial remission following re-induction therapy, he underwent a second BMT from another unrelated donor, and experienced complete remission with grade II acute graft-versus-host disease and moderate chronic graft-versus-host disease. He remains alive in complete remission more than 71 months after the second BMT. These results suggested that donor change at the second transplantation may represent a considerable therapeutic option for patients with relapsed BPDCN.